Aluminum foil as a substrate for metal enhanced fluorescence of bacteria labelled with quantum dots, shows very large enhancement and high contrast - Alisher Sultangaziyev; Aktilek Akhmetova; Zhanar Kunushpayeva; Alisher Rapikov; Olena Filchakova; Rostislav Bukasov (Sensing and Bio-Sensing Research, 2020)
Very high surface/metal enhanced fluorescence was observed for E. coli single bacteria cells labeled with composite CdSeS/ZnS quantum dots (QDs) on three substrates: aluminum foil, aluminum film and gold film. The enhancement factors relative to maximum fluorescence intensity on glass for those substrates were in the range of several hundred (up to 500) for two-excitation wavelengths 532 and 633 nm. Contrast as a ratio of signals from QD labeled to signals of QD unlabeled (control) cells was also in the range of 100 s for those substrates and the highest contrast of 370 was observed on Al film. When CdTe QDs were used for labelling cells on all substrates or when fluorescence from cells with both QDs was measured on silver film, low or no enhancement was observed. Overall, untreated aluminum foil demonstrated great potential as low-cost substrate for surface/metal enhanced fluorescence, which delivers even more reproducible signal than gold film. Keywords: Surface enhanced fluorescence, Metal enhanced fluorescence, Quantum dots, Aluminum foil, Enhancement facor, Bacteria, E. coli, QD toxicity, Contrast, Single bacterial cell detection